Rural Participatory Innovation Lab: toward a sustainable territory - Clavijo, Neidy Lorena; Rodríguez Ramírez, Luz Angela; Mañunga Rivera, Alexandra; Bernal, Angie Paola; Mesa, Ana María; Vanegas Cubillos, Martha (2024)
Participatory rural innovation processes provide the  opportunity to work alongside local communities  to develop alternatives that align with their social,  economic, ecological, and cultural contexts, where  they, in collaboration with supporting entities, take on  the roles of co-designers and managers of sustainable  agroecosystems. In this document, we present the  results of the participatory prioritization of bottom-up  innovations toward sustainable, resilient, and low- emission food systems in La Montañita, Caquetá,  Colombia. The necessary transformations in food  systems were organized around three topics identified  by stakeholders as key for just transformations: (1)  improving soil fertility, (2) improving the connectivity and internal structure of farms, and (3) strengthening  strategies for the commercialization of agroecological  products.